Discrete Element Analysis of Grouting Reinforcement and Slurry Diffusion in Overburden Strata - Pengfei Guo; Weiquan Zhao; Yahui Ma; Huiling Gen (Applied Sciences)
Research on the grouting reinforcement mechanism of overburden is constrained by the concealed and heterogeneous nature of geotechnical media, posing dual challenges in theoretical analysis and process visualization. Based on discrete element numerical simulations and laboratory tests, an analytical model for grouting reinforcement in overburden layers is developed, revealing the influence of grouting pressure on slurry diffusion shape and distance. The results indicate the following: (1) Contact parameters of overburden and cement particles were obtained through laboratory tests. A grouting model for the overburden layer was established using the discrete element method. After optimizing particle coarsening and the contact model, the simulation more accurately represented slurry diffusion characteristics such as compaction, splitting, and permeability. (2) By monitoring porosity and coordination number distributions near grouting holes before and after injection using circular measurement, the discrete element simulation clearly visualizes the slurry reinforcement range. The reinforcement mechanism is attributed to the combined effects of pore structure compaction (reduced porosity) and cementation within the overburden (increased coordination number). (3) Based on slurry diffusion results, a functional relationship between slurry diffusion radius and grouting pressure is established. Error analysis shows that the modified formula improves the goodness of fit by 34–39% compared to the classical formula (Maag, cylindrical diffusion). The discrete element analysis method proposed in this study elucidates the mechanical mechanisms of overburden grouting reinforcement at the particle scale and provides theoretical support for visual evaluation of concealed structures and optimization of grouting design.